Minimally Invasive Robotic Versus Open Fluoroscopic-guided Spinal Instrumented Fusions: A Randomized Controlled Trial - Hyun, Seung-Jae; Kim, Ki-Jeong; Jahng, Tae-Ahn; Kim, Hyun-Jib (Spine (Philadelphia, Pa. 1976), 2017)
A prospective randomized clinical trial. To compare the impact of robotic guidance in a minimally invasive spine surgery (MIS) to a fluoroscopy-guided open approach in lumbar fusions. MIS requires a protracted learning curve and excessively exposes the patient and surgical team to harmful radiation. Robotic-guidance has been shown to improve accuracy and radiation in most studies, but there is conflicting prospective data. Patients indicated to undergo a 1 or 2 level spinal fusion were randomized between robotic-guided MIS (RO) and fluoroscopic-guided open surgery (FA). Patient demographics and outcomes were recorded. Thirty patients were recruited to each arm. Average age was 66.7 years, 71.5% were females, and average body mass index was 25.2. Thirty-five levels were instrumented with 130 pedicle screws in RO versus 40 levels with 140 screws in FA, or 4.3 and 4.7 screws per surgery, respectively. Use of fluoroscopy was 3.5 versus 13.3 seconds in the RO and FA respectively (P < 0.001). C-arm output in mSv was 0.13 versus 0.27 in the RO and FA respectively (P = 0.015). By thermoluminescent dosimeters, the average per-screw radiation in the RO arm was 37.5% of that in the FA arm, demonstrating a mean reduction of 62.5% in use of radiation. There was no difference in the improvement in Visual Analog Scale scores for back and leg or the Oswestry Disability Index. All screws were accurate in RO whereas two screws breached (>2 mm and >4 mm) in FA (P = 0.500). One proximal facet violation occurred in the study, it was in FA (P = 1.000). The average distance from the proximal facets was 5.8 versus 4.6 mm in the RO and FA respectively (P < 0.001). The average length of stay was 6.8 versus 9.4 days in RO compared with FA (P = 0.020). MIS using robotic-guidance significantly reduced radiation exposure and length of stay. Patient outcomes were not affected by the surgical technique. 1.